2017
DOI: 10.1002/adfm.201700212
|View full text |Cite
|
Sign up to set email alerts
|

DNA Lipoplex‐Based Light‐Harvesting Antennae

Abstract: Natural light‐harvesting complexes are operated through the well‐designed self‐assembly of pigments with large protein complexes in a thylakoid lipid bilayer. However, a long‐range, directed transfer of excitation energy has not been achieved in artificial systems because the nanoscale arrangement of chromophores into stable micrometer‐scale structures is highly challenging. Here the multiscale assembly of chromophores for excited energy transfer through the arrangement of chromophores on nanoscale DNA templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Recently, we reported that some oppositely charged globular proteins can induce the structural changes of pre-formed charged lipid nanovesicles into multilamellar structures through polyionic interaction under certain conditions [18,19]. Our approach is similar to nucleic acid-lipid ionic complexation, where negatively charged nucleic acids are intercalated into the interstitial space of cationic lipid vesicles to generate closely packed arrays through spontaneous phase conversion [20][21][22]. However, protein-lipid complexation is technically more challenging as the precise control of the intermolecular interaction between proteins and the lipid membranes of nanovesicles is complicated because of the low and heterogeneous surface charge density of proteins.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, we reported that some oppositely charged globular proteins can induce the structural changes of pre-formed charged lipid nanovesicles into multilamellar structures through polyionic interaction under certain conditions [18,19]. Our approach is similar to nucleic acid-lipid ionic complexation, where negatively charged nucleic acids are intercalated into the interstitial space of cationic lipid vesicles to generate closely packed arrays through spontaneous phase conversion [20][21][22]. However, protein-lipid complexation is technically more challenging as the precise control of the intermolecular interaction between proteins and the lipid membranes of nanovesicles is complicated because of the low and heterogeneous surface charge density of proteins.…”
Section: Introductionmentioning
confidence: 97%
“…[13][14][15][16][17][18][19][20][21][22] In such systems, light is collected by precisely arranged donor chromophores and the absorbed energy is transferred to a suitable acceptor. [23][24][25][26][27][28][29][30] The light-harvesting properties resulting from the supramolecular assembly of phenanthrene and pyrene molecules within the scaffold of the DNA duplexes was demonstrated before. 17 In this type of LHC, the phenanthrene units serve as donor chromophores.…”
mentioning
confidence: 92%
“…Accordingly, biomimetic approaches have been attempted using natural photosystems as an efficient light-harvesting model to develop photoelectronic and photochemical materials. , The synthesis and supramolecular self-assembly of pigments have been extensively reported using graft copolymers, dendrimers, and biological macromolecules (e.g., DNA, peptides, proteins, viruses, and lipid vesicles) as templates that guide the organization of pigments on the nanoscale. However, it is very challenging and time-consuming to fabricate such sophisticated supramolecules for efficient energy transfer, as found in natural light-harvesting antennae, in a reasonable yield.…”
Section: Introductionmentioning
confidence: 99%